A case of a rare hibernoma tumour and a brief literature review - Gauci, Kristen; Debono, Fabian; Gauci, Fiona; Panzavecchia, Francesca (International Journal of Research in Orthopaedics, 2023)
Hibernomas refer to benign tumours of immature adipose tissue known a brown fat. They are most commonly found in areas where brown adipose tissue is still present in adulthood such as the shoulder, back, neck, best, arm and abdomen. This case study describes a 60 year old male who presented with a growing 15 mm lump in the right forearm. On examination, tenderness in the area surrounding the mass was elicited. A magnetic resonance image of the right forearm was performed which reported a large intramuscular lipomatous tumour within the brachioradialis muscle, in close relation to the neuromuscular bundle. Surgical excision was performed successfully. Histology was consistent with a diagnosis of a hibernoma tumour. The patient healed well with no evidence of infection or recurrence on follow up.